Enzymes in Food Technology Improvements and Innovations (Springer Singapore, 2018)
The integration of enzymes in food processing is well known, and dedicated research is continually being pursued to address the global food crisis. This book provides a broad, up-to-date overview of the enzymes used in food technology. It discusses microbial, plant and animal enzymes in the context of their applications in the food sector; process of immobilization; thermal and operational stability; increased product specificity and specific activity; enzyme engineering; implementation of high-throughput techniques; screening of relatively unexplored environments; and development of more efficient enzymes. Offering a comprehensive reference resource on the most progressive field of food technology, this book is of interest to professionals, scientists and academics in the food and biotech industries.